2016
DOI: 10.1038/ncomms13058
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the catalytic CO hydrogenation to straight- and long-chain aldehydes/alcohols and olefins/paraffins

Abstract: The catalytic CO hydrogenation is one of the most versatile large-scale chemical syntheses leading to variable chemical feedstock. While traditionally mainly methanol and long-chain hydrocarbons are produced by CO hydrogenation, here we show that the same reaction can be tuned to produce long-chain n-aldehydes, 1-alcohols and olefins, as well as n-paraffins over potassium-promoted CoMn catalysts. The sum selectivity of aldehydes and alcohols is usually >50 wt% whereof up to ∼97% can be n-aldehydes. While the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(161 citation statements)
references
References 30 publications
10
138
2
Order By: Relevance
“…Unlike oriented Co single crystals, such Co bulk provides an appropriate texture with low yet sufficient specific surface area for high-pressure catalytic tests, as reported, for example, in Ref. [4].…”
Section: Preparation Of Supported Catalystsmentioning
confidence: 95%
See 1 more Smart Citation
“…Unlike oriented Co single crystals, such Co bulk provides an appropriate texture with low yet sufficient specific surface area for high-pressure catalytic tests, as reported, for example, in Ref. [4].…”
Section: Preparation Of Supported Catalystsmentioning
confidence: 95%
“…Recent studies have also demonstrated the production of long chain terminal alcohols, aldehydes and/or short chain olefins with high selectivity from syngas as, for example, described in Ref. [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Higher oxygenate synthesis over cobalt based catalysts are generally carried out at low temperature ranging from 170°C to 280°C [5,19,34,51] since cobalt carbide decomposes above 300°C [52], so the oxygenate selectivity is lower at high temperatures. However, cobalt carbide on the MOF-mediated synthesized catalysts is maintained after reaction at 325°C, thus, the catalysts in this study showed high selectivity to C 2-C 6 oxygenates (36% at 325°C for 5K-Co 3 O 4 ).…”
Section: Z Wang Et Almentioning
confidence: 99%
“…Forming Co 2 C on the surface of a cobalt catalyst can provide both metallic cobalt and Co 2 C sites in close proximity, as is required for oxygenate formation. Although the role of Co 2 C in CO hydrogenation is not certain, there are several studies that detected the formation of cobalt carbide on catalysts with high oxygenate yields [20,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 98%
“…While there is general agreement that a polymerization‐type reaction mechanism is in operation, the question for the chemical nature of the inserting monomer and the respective target chemical bonds have been a matter of debate for decades . This lack of established knowledge is particularly inhibiting in view of emerging FT process variants which aim at directing the synthesis to light olefins,, for example, or long‐chain alcohols and aldehydes through the use of advanced catalyst preparation techniques. Notwithstanding the deficits in molecular‐level understanding, the various opinions on the mechanistic pathways may be categorized by either claiming immediate or delayed carbon monoxide dissociation while composing hydrocarbon skeletons along with their functionalization.…”
Section: Figurementioning
confidence: 99%